(untitled) (Psychology Travelogs, 2025)
The article explores emotional self-regulation as a vital factor in maintaining the mental health of future psychologists. It emphasizes the importance of this ability in addressing modern challenges, such as stress, emotional exhaustion, and academic overload, which significantly affect students in psychology programs. Emotional self-regulation is analyzed through its psychological, social, and physiological dimensions, with particular attention to the student age as a critical period for developing these skills. The authors highlight the role of emotional self-regulation in building resilience to stress, fostering emotional intelligence, and ensuring professional adaptability. Future psychologists often face emotionally demanding topics and high academic expectations, which require not only theoretical knowledge but also the ability to manage their emotional states. Self-regulation is presented as a key resource for maintaining personal well-being and a critical professional skill for effective client interaction, empathy, and emotional control. Research conducted among psychology students revealed significant variability in their self-regulation skills. While some students demonstrated adaptability, empathy, and emotional sensitivity, others showed high levels of anxiety, emotional rigidity, and dependence on external support. This variability highlights the need for targeted interventions to enhance emotional self-regulation. The authors propose a structured program to develop emotional self-regulation, integrating theoretical knowledge with practical techniques. The program includes relaxation practices, mindfulness strategies, stress management methods, and emotional intelligence training. It also involves role-playing exercises and stress simulations to help students adapt to real-world challenges.